1988
DOI: 10.2466/pr0.1988.63.2.659
|View full text |Cite
|
Sign up to set email alerts
|

Adaption-Innovation and the Torrance Tests of Creative Thinking: The Level-Style Issue Revisited

Abstract: Kirton has asserted that his measure of creative style, Kirton Adaption-Innovation Inventory, is discrete or orthogonal to level measures of creativity. This study used a well-established measure, the Torrance Tests of Creative Thinking, on a relatively larger sample than in previous studies. Scores for 132 (40 men, 92 women) college students on Kirton's measure were significantly correlated with scores on Torrance's Fluency, Flexibility, and Originality subtests. Further, t tests showed a significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
40
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 17 publications
10
40
0
2
Order By: Relevance
“…The KAI test predominantly differentiates between creative styles, a goal similar to that of this study, but has also been shown to bear some correlation to overall creative level (Isaksen & Puccio, 1988). As such, it is a highly appropriate measure for comparison.…”
Section: The Coding Processmentioning
confidence: 76%
See 2 more Smart Citations
“…The KAI test predominantly differentiates between creative styles, a goal similar to that of this study, but has also been shown to bear some correlation to overall creative level (Isaksen & Puccio, 1988). As such, it is a highly appropriate measure for comparison.…”
Section: The Coding Processmentioning
confidence: 76%
“…There are strong, significant correlations between the creative test score and expansion (P<0.0098 against cross entity type tasks; P<0.0172 against later stage expansion; Table 13). These show that people who are identified according to Kirton (1976) as innovators (a characteristic that has been linked with higher levels of creativity (Goldsmith & Matherly, 1987;Isaksen & Puccio, 1988)) will complete a higher proportion of the later stages in a more expansive way, particularly within cross entity type tasks. Therefore it is highly likely (within the bounds of this sample size) that expansion is suitable as an indicator of creative behaviour and so that the coding scheme is identifying that which it was designed to identify, creative behaviour within the later stages of the design process.…”
Section: External Data and Correlationsmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been suggested that in groups with diverse levels of talent and salient characteristics willingness to creatively participate may be an important mediating variable that gives strength to work groups' acceptance and shapes their subsequent cognitive processes (Milliken et al, 2003). Historically, creative personality and creative talent have been given a lot of attention (Isaksen and Puccio, 1988;MacKinnon, 1965), but surprisingly little is known about employees' willingness to creatively participate from their own individual perspective.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that in groups with diverse levels of talent and salient characteristics willingness to creatively participate may be an important mediating variable that gives strength to work groups' acceptance and shapes their subsequent cognitive processes (Milliken et al, 2003). Historically, creative personality and creative talent have been given a lot of attention (Isaksen and Puccio, 1988;MacKinnon, 1965), but surprisingly little is known about employees' willingness to creatively participate from their own individual perspective.To address the above gaps in research on employee willingness to creatively participate, this study aims to contribute to extant literature in three ways. First, we build on previous related research to progress the conceptualization of factors that potentially affect willingness to creatively participate with either positive or negative outcomes.…”
mentioning
confidence: 99%